2022
DOI: 10.1007/s11227-022-04823-7
|View full text |Cite
|
Sign up to set email alerts
|

Prioritized scheduling technique for healthcare tasks in cloud computing

Abstract: The Internet-of-things (IoT) plays a significant role in healthcare monitoring, where the IoT Cloud integration introduces many new opportunities for real-time remote monitoring of the patient. Task scheduling is one of the major challenges in cloud environment. Solving that problem reduces delay, missed tasks, and failure rate, and increases the guarantee ratio. This paper proposes a new task scheduling and allocation technique: Prioritized Sorted Task-Based Allocation (PSTBA) for healthcare monitoring implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The proposed method increases scheduling accuracy, enhancing healthcare systems' performance and effectiveness. Elshahed et al [21] proposed a new prioritized sorted task-based allocation (PSTBA) for healthcare monitoring systems. The virtual machine is used here to perform a particular task in monitoring systems.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed method increases scheduling accuracy, enhancing healthcare systems' performance and effectiveness. Elshahed et al [21] proposed a new prioritized sorted task-based allocation (PSTBA) for healthcare monitoring systems. The virtual machine is used here to perform a particular task in monitoring systems.…”
Section: Related Workmentioning
confidence: 99%
“…These studies aim to explore the potential bene ts of cloud computing for different application areas and to identify the challenges and opportunities associated with this approach. Some examples of these studies can be found in [20][21][22][23][24][25]. Overall, these efforts are aimed at advancing the development of cloud-based applications and improving their effectiveness and e ciency.…”
Section: Related Workmentioning
confidence: 99%
“…Depending on the rate of congestion and priority of the data sensed, transmission is balanced using queuing or delivery as modeled in the decision mode. For real-time remote monitoring of the patient, Elshahed et al [17] propose a new task scheduling and allocation technique for healthcare monitoring implemented in IoT cloud-based architecture. The proposed technique performs a prioritized sorted task-based allocation scheme for selecting the best virtual machine to execute the health task, solving the problem of delay, missed tasks, and failure rate, and the guarantee ratio.…”
Section: Scheduling On Iomtmentioning
confidence: 99%